Empowering Members: Launching Risk-Aware Overdraft Systems to Enhance Financial Resilience (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The growing rate of financial instability among the banking members has highlighted the need to have intelligent overdraft systems that reduce the risks and maintain a trade of between accessibility and risk reduction. The study presents a risk-sensitive overdraft system which can enable members by using predictive analytics, adaptive eligibility modeling, and dynamic product strategy combination. The system allows making decisions regarding overdraft eligibility and transaction risk scoring in near-real-time. Its methodology uses risk modeling through machine learning, with historical data of transactions and behavioral factors to determine the financial strength of the member. The Kafka-based event stream will work as the coordinator of the communication between the risk evaluation modules and the backend services, whereas the analytical foundation is BigQuery that will be used to perform massive data aggregation and computation of features. Whimsical and Jira were used as systems architecture and sprint-based agile implementation tools to develop the prototype, respectively. As the analysis of the results shows, the given system will provide excellent operational and financial results in all significant indicators. The model has a reduction of 7.9% in NSF events that is realized to show improved accuracy in the prediction of overdraft risk and the minimization of unnecessary declines. It also allows approving about 10 million transactions, which demonstrates the greater efficiency of systems and the enhanced experience of the members. The 97% recovery in 15 days is a strong improvement in the repayment performance. More than that, the system leads to increased participation of members, as 28% of qualified users subscribe to the overdraft service. Finally, incremental interchange increase by 2% indicates quantifiable revenue improvements due to improved decisions of approvals. On the whole, the outcomes of these studies confirm the efficiency of the given strategy.
Keywords: Banking Systems; Risk Modeling; Member Eligibility; Product Strategy; Backend Engineering; Financial Resilience